Universal thermoelectric generator with heat removal by water tanks - Anatychuk, L.I.; Lysko, V.V.; Konstantynovych, I.A.; Havryliuk, M.V. (Journal of Thermoelectricity, 2024)
The work describes the design of a universal thermoelectric generator that can operate from any heat source - heated flat surfaces of stoves, gas or multi-fuel tourist primus, open flame, etc. The electrical energy received from the generator with a power 20-40 W provides autonomous power supply for various low-power radio electronic equipment, portable radio stations, mobile communication systems, lighting, as well as charging universal mobile batteries - power banks. To remove heat from the cold side of thermoelectric modules, tanks with water are used, which can be used for domestic purposes. The results of bench and field experimental studies of the developed generator are presented. Bibl. 30, Figs. 10, Table. 1.